Osteoporosis in Patients With Respiratory Diseases - Ma, Yue; Qiu, Shui; Zhou, Renyi (Frontiers in Physiology, 2022)
Climate change, environmental pollution and virus epidemics have sharply increased the number of patients suffering from respiratory diseases in recent years. Prolonged periods of illness and drug use increase the occurrence of complications in these patients. Osteoporosis is the common bone metabolism disease with respiratory disturbance, which affects prognosis and increases mortality of patients. The problem of osteoporosis in patients with respiratory diseases need more attention. In this review, we concluded the characteristics of osteoporosis in some respiratory diseases including COPD, asthma, COVID-19, tuberculosis and lung cancer. We revealed that hypoxia was the common pathogenesis of osteoporosis secondary to respiratory diseases; malnutrition and corticosteroid abuse drave the progression of osteoporosis; tuberculosis and cancer also invaded bone tissue and reduced bone strength by direct infiltration. For the treatment of osteoporosis in respiratory patients, oral optimized bisphosphonates were the best treatment modality. Vitamin D was a necessary supplement, both for calcium absorption in osteogenesis and for improvement of respiratory lesions. Reasonable adjustment of the dose and course of corticosteroids according to the etiology and condition of patients is beneficial to prevent the occurrence and development of osteoporosis. Additionally, HIF-1α was an potential target for the treatment of osteoporosis in respiratory patients, which could be activated in hypoxia condition and involved in the process of bone remodeling.